FLIPPING ACTIVITY AND UNDERPRICING PHENOMENON IN INDONESIA STOCK EXCHANGE - Dewi, Atika Nisrina; Asri, Marwan (Jurnal Reviu Akuntansi dan Keuangan)
Underwriters, as well as issuers, show ambiguity toward the flipping activity or selling initially public offered stocks (IPO stocks) in the first trading day. On one side, they are naturally against the flipping activity because it is considered to decrease IPO performances, especially in the case of weak offerings. However, flipping activity is also needed to show liquidity of the IPO stock in the secondary market. Several studies indicate that there is a relationship between flipping activity and underpricing phenomenon. Previous research also shows that by studying flipping activity, we can also learn about disposition effect in the primary market. In this study we investigate the relationship between flipping activity and underpricing phenomenon and the presence of disposition effect in Indonesian primary market. Further, the study also test whether the investors’ decision to flip the underpricing stock is a rational decision or because of the fear of regret. The result shows that disposition effect is not found in Indonesian primary market. We also found that there are different level of flipping activities in different level of underpricing, and investor’s decision to flip the underpricing stocks is actually a rational decision.